The RNA m5C methyltransferase NSUN1 modulates human malaria gene expression during intraerythrocytic development - Tang, Ruoyu; Fan, Yanting; Lu, BinBin; Jiang, Qunfeng; Cheng, Xinyu; Zhang, Zuping; Shen, Li; Shang, Xiaomin (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionPlasmodium falciparum is the most damaging malaria pathogen and brings a heavy burden to global health. Host switching and morphological changes in P. falciparum are dependent on an effective gene expression regulatory system. C5 methylation of cytosines is a common RNA modification in eukaryotes, and the NSUN family are essential m5C modification executors. Currently, little is known about this family in Plasmodium spp. In this study, we focus on exploring the function of PfNSUN1 protein.MethodsAn efficient CRISPR/Cas9 gene editing technique was applied to construct the PfNSUN1 knockdown strain. The knockdown efficiency was confirmed by growth curves and western blot experiments. The knockdown transcriptome data was acquired to find differentially expressed genes, and target genes of PfNSUN1 protein were identified by RNA immunoprecipitation and high-throughput sequencing experiments.ResultsThe efficiency of PfNSUN1 protein down-regulated was about 34%. RNA-seq data revealed that differentially expressed genes were mainly down-regulated. And there were 224, 278, 556 genes that were down-regulated with more than 2-fold changes and p-adj<0.05 at ring, trophozoite and schizont stages, respectively. PfNSUN1 protein was significantly enriched on 154 target genes, including 28S ribosomal RNA and pfap2-g5 transcription factor.DiscussionPfNSUN1 is a crucial RNA post-transcriptional modification protein in P. falciparum. It plays a pivotal role in regulating gene expression and parasite growth by targeting 28S ribosomal RNA and pfap2-g5 transcription factor.